High Fe-Loading Single-Atom Catalyst Boosts ROS Production by Density Effect for Efficient Antibacterial Therapy - Si Chen; Fang Huang; Lijie Mao; Zhimin Zhang; Han Lin; Qixin Yan; Xiangyu Lu; Jianlin Shi (Nano-Micro Letters)
Highlights Fe single-atom catalysts (h3-FNCs) with high loading, high catalytic activity and high stability were synthesized via a method capable of increasing both the metal loading and mass-specific activity by exchanging zinc with iron. The “density effect,” derived from the sufficiently high density of active sites, has been discovered for the first time, leading to a significant alteration in the intrinsic activity of single-atom metal sites. The superior oxidase-like catalytic performance of h3-FNCs ensures highly effective bacterial eradication.